Analysis of genetic relationships of genotypes of the genus Rosa L. from the collection of Nikita Botanical Gardens using ISSR and IRAP DNA markers - I. I. Suprun; S. A. Plugatar; I. V. Stepanov; T. S. Naumenko (Вавиловский журнал генетики и селекции, 2020)
In connection with the development of breeding and the creation of new plant varieties, the problem of their genotyping and identification is becoming increasingly important, therefore the use of molecular methods to identify genetic originality and assess plant genetic diversity appears to be relevant. As part of the work performed, informative ISSR and IRAP DNA markers promising for the study of genetic diversity of the Rosa L. genus were sought and applied to analysis of genetic relationships among 26 accessions of the genus Rosa L. from the gene pool collection of Nikita Botanical Gardens. They included 18 cultivated varieties and 8 accessions of wild species. The species sample included representatives of two subgenera, Rosa and Platyrhodon. The subgenus Platyrhodon was represented by one accession of the species R. roxburghii Tratt. Cultivated roses were represented by varieties of garden groups hybrid tea, floribunda, and grandiflora. The tested markers included 32 ISSRs and 13 IRAPs. Five ISSR markers (UBC 824, ASSR29, 3A21, UBC 864, and UBC 843) and three IRAPs (TDK 2R, Сass1, and Сass2) were chosen as the most promising. They were used for genotyping the studied sample of genotypes. In general, they appeared to be suitable for further use in studying the genetic diversity of the genus Rosa L. The numbers of polymorphic fragments ranged from 12 to 31, averaging 19.25 fragments per marker. For markers UBC 864 and UBC 843, unique fingerprints were identified in each accession studied. The genetic relationships of the studied species and varieties of roses analyzed by the UPGMA, PCoA, and Bayesian methods performed on the basis of IRAP and ISSR genotyping are consistent with their taxonomic positions. The genotype of the species R. roxburghii of the subgenus Platyrhodon was determined genetically as the most distant. According to clustering methods, the representative of the species R. bengalensis did not stand out from the group of cultivated varieties. When assessing the level of genetic similarity among the cultivated varieties of garden roses, the most genetically isolated varieties were ‘Flamingo’, ‘Queen Elizabeth’, and ‘Kordes Sondermeldung’; for most of the other varieties, groups of the greatest genetic similarity were identified. This assessment reflects general trends in phylogenetic relationships, both among the studied species of the genus and among cultivated varieties.